Zarządzanie wiedzą w bibliotece. Rola wiedzy i nauki w nowoczesnej organizacji = Knowledge management in libraries. The role of knowledge and science in a modern organization - Adaszyńska, Ewa (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
Dynamic reality together with a difficult to predict environment force people to be creative and to undergo constant changes that can ensure the development and success of an organization and its members. The basis of these transformations is knowledge ? a new dominant resource which determines the competitive advan- tage of organizations such as libraries. Competitiveness is the ability to constantly improve, create and implement modern organizational solutions and technologies as well as new concepts, services and products. It is based on creative, flexible people whose knowledge and ideas are used for new, innovative solutions.People are the source of organizational knowledge, and new competences are built based on this knowledge. It changes over time, which is why constant learning is required, so that one can gain and create new knowledge from our own experience, but also from the others, and share it with one another. Knowledge is a strategic resource in the new society, used to achieve the assumed goals, which requires appropriate management, a special approach to the strategy and structure of an organization, personnel policy, managerial skills and communication systems, because it is immaterial. It must be closely related to the processes of managing people. This article discusses the definitions of knowledge, its types, classification and usage. It introduces issues related to knowledge management, its concepts and approaches as well as related processes and technologies. It combines knowledge management with non-material organizational resources and intellectual capital of its employees, especially in the context of classified knowledge. It touches on the issues of organizational culture and a learning organization. It moves the discussed issues to the library environment and space to understand andorganize the complexity of the problem. Knowledge management is included in modern organizational management tools. Taking into account the positions presented on definitional issues, it is treated as a resource, process, strategy, benefits creation tool as well as a management method.
Keywords: zarządzanie wiedzą; biblioteka; wiedza organizacyjna; kapitał intelektualny; innowacyjność organizacji; kultura organizacyjna; knowledge management; library; organizational knowledge; intellectual capital; organizational innovation; organizational culture